Romania - Functional Review : Regional Development and Tourism - World Bank (Washington, DC, 2013)
The Functional Review of the Ministry of Regional Development and Tourism (MRDT FR) assesses the key functional strengths and weakness of MRDT with respect to its mandate and recommends actions that can help strengthen its efficiency and effectiveness. The review covers the main general directorates (DGs) and departments of MRDT, as well as related institutions such as URBAN-INCERC and the National Housing Agency. The report has six main chapters in addition to the executive summary: Introduction, Overview of MRDT, Policy Management, Operational Management, Budget and Financial Management, and Public Procurement.